Minerals Identification and Analysis of Granite Rocks in South Aceh District Using X-Ray Diffraction (XRD) - Bakruddin Bakruddin; Arnold Ricardo Sembiring (LPPM Politeknik Aceh Selatan, 2019)
The potential of non-metallic natural resources in South Aceh Regency is very abundant, one of which is granite rock. Granite rock is igneous rock that can be used for a variety of household and industrial products. This rock has certain characteristics based on its constituent mineral structure. South Aceh granite rocks are scattered in two different locations namely Samadua District and Sawang District. This research was conducted to determine the constituent mineral phase using the X-Ray Diffraction method. The results of testing and analysis showed that granite rock samples taken from Lhok pawoh village contained Quartz (SiO2) as the dominant phase, while the minor phase was Aluminum oxide (Al2O3). While the granite rock samples taken from Ujung Karang Village have Quartz (Sio2) as the dominant phase, while the minor phase is the dominant mineral phase contained in the dominant phase, namely Aluminum oxide (Al2O3). From the two samples above the high diffraction pattern is owned by rock samples from Ujung Karang Village.